Research Joint Ventures and Technological Proximity - Aranja Müller; Alexandra Zaby (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We study research joint ventures (RJV) given that knowledge spillovers depend positively on the technological proximity between rms. Possible scenarios differ in the intensity of collaboration, i.e., the (non)coordination of research activities and the extent of knowledge sharing. The investigation of bilateral RJVs in an oligopolistic market allows to distinguish e ects for insider and outsider rms. Our central ndings are (i) RJVs do not generally outperform competitive research with respect to innovative output, and social welfare. (ii) Technological proximity and the intensity of cooperation play a decisive role for the private and social favorability of a RJV. (iii) Joint research combined with complete knowledge sharing outperforms less intensive cooperation forms.
Keywords: D43; L13; O31; 330